Sublethal exposure to imidacloprid in commercial Apis mellifera colonies in early spring: performance of honey bees and insecticide transference between in-hive products - Michlig, Melina Paola; Pacini, Adriana Cecilia; Merke, Julieta; Orellano, Emanuel; Brasca, Romina; Repetti, María Rosa (Springer, 2023)
Honey bees have an important role in ecosystems as pollinators. However, in recent years, bee populations have declined, with habitat destruction, pesticide use, and climate change contributing to the decline. One of the most important risk factors is the use of neurotoxic pesticides, such as neonicotinoids. The aim of this work was to study the effects of imidacloprid in commercial Apis mellifera L. colonies artificially fed with syrups spiked with this insecticide and its possible transfer among in-hive products such as honey and larvae. For this purpose, 30 colonies were placed in the same apiary; once a week for 7 weeks in early spring, each colony was fed with 0.5 L of syrup with the following doses of imidacloprid: 0, 15, 30, 120, and 240 µg kg−1. The colony strength was evaluated by monitoring: the number of adult bees and brood combs, queenlessness, unhealthy colonies (by detection of Nosema spp. spores and European foulbrood), as well as pollen and honey storage. Worker bees, larvae, honey, and beeswax were sampled to evaluate imidacloprid transfer within the hive. Trends in the persistence of the compound showed that up to 60% of the parent (not metabolized) was stored in honey, and the absence of residues in the larvae suggests that they were not exposed. Another result showed a certain impact in the honey reserves and honey yield with a reduction of this resource in the colonies exposed to imidacloprid.